Financial And Non-Financial Charateristics And Their Iinfluence On Transfer Pricing - Gumilang, Gabiela; Muchtar, Masruri; Sihombing, Pardomuan Robinson (WIM Solusi Prima, 2024)
It is a common thing that companies try to find ways to reduce the tax burden that must be paid in order to increase company profits. One way that is most often done is by implementing transfer pricing practices. This research aims to analyze the influence of leverage, tunnel incentives, and good corporate governance in influencing company activities in carrying out transfer pricing. The research method used in this research is the panel data regression method (rando-effect model). The data used in this writing is secondary data from manufacturing company financial reports available on the Indonesia Stock Exchange website for the period 2020 - 2022. In this research it was found that leverage has a significant influence on the company's transfer pricing indications. Meanwhile, foreign share ownership and the number of independent commissioners do not have a significant effect on transfer pricing indications. It is hoped that the results of this research will draw attention to the fact that transfer pricing indications can cause losses for the state. Reducing the amount of tax paid by companies can be done through good financial management, not through tax avoidance.